(3JGQjN GdEQgGH GdCeQjcj (B:s (3GdchcdGcS cdGf (B/s - (3Q(B.(3a(B. (3GjaGfha,a(B. (3djSfjaScj s; (3ZSGfs ((3ShQjI (B:s (3OGQ GdMhGQ ddfTQ h GdJhRjY ,s, 1983)
(3fLO aj gPG GdcJGH GdPj jbOe aj JGQjN GdcdGfjI Gced UhQI dJGQjN GdhdGjGJ GdeJMOI GdCeQjcjI efP CcKQ ef bQf h MJi fgGjI GdSHYjfGJ ef gPG GdbQfs
Keywords: (3GdEQgGH GdCeQjcjs; (3JGQjNs